Non-COVID-19 Cutaneous Mucormycosis from a Plastic Surgical Perspective - Vimalendu Brajesh; Sneha Sharma; Aditya Aggarwal; Sukhdeep Singh; Sanjay Mahendru; Hardeep Singh; Ankit Jain; Rahul Jain; Rakesh Kumar Khazanchi (Indian Journal of Plastic Surgery)
Background Cutaneous mucormycosis is a rare and fulminant infection associated with high mortality. Plastic surgeons come across this infection in the settings of road traffic accidents, surgical site infections, and as a secondary infection with underlying bacterial soft tissue infections. Due to this infection's rarity and aggressive course, it is essential to initiate prompt multidisciplinary management at the first presentation. With this study, we aim to present a protocol for managing the condition.